THE APPLICATION OF NATURAL DYES TO BATIK USING MANGROVE SPESIES RHIZOPORA STYLOSA, SOGA TINGI (CERIOPSTAGAL) AND INDIGOFERA - Paryanto Paryanto; Sunu Herwi Pranolo; Ari Diana Susanti (Jurnal Inovasi Teknik Kimia, 2021)
Technological advance leads the natural dyes to be eroded by the synthetic one. Synthetic colorant has advantages of salient, more uniform color and more practical use. Meanwhile, the disadvantage of it is much metal content harmful to the environment. The natural colorant is colorant (pigment) derived from plant, animal or mineral sources. The advantage of natural dyes is that it is more environment-friendly because it is not poisonous and safe for health. The disadvantage of it is storage difficulty. When natural dyes in liquid form is stored too long, it will be decomposed easily. For that reason, it should be stored in powder form.The method used to get natural dyes was extraction with a batch manner. The extraction was carried out with basic material-to-solvent ratios of 1:10, 1:7, and 1:5. The basic materials used were mangrove spesies rhizopora stylosa, Soga Tingi, and Indigofera. The best extract was obtained with a ratio of 1:5 for all basic materials. The powder was prepared by feeding the extracting solvent into a spray dryer so that the natural colorant powder was obtained. The application of colorant powder was used at 1 gram/100 ml, 2 gram/100 ml, 2 gram/100 ml, 4 gram/100 ml, and 5 gram/100 ml. The immersing with natural colorant was conducted in 2 conditions: extract and powder are immersing were carried out 5 times with each submerging of 15 minutes and dried. Then, fixation (color-locking) was done to batik. The fixer employed was tunjung (changing the color of batik into the darker one), alum (maintaining the batik’s color), and lime (change batik color into the brighter one). The fixated batik cloth was then examined for its fading against washing using launder meter and against rubbing using crock meter. The result of the examination was analyzed using a staining scale and greyscale. The examination using the staining scale was divided into 2: wet and dry rubbings. From the result of the wet and dry rubbing test, it was obtained the best result with tingi colorant, alum fixer solution, and powder condition. Meanwhile, on the greyscale, it was obtained the best result with tingi colorant, alum fixer, and powder condition. So, it could be concluded that the optimum application of powder to batik cloth was 4 gram/100 ml water and 5 times immersing. The best result of fading resistance against washing and rubbing was tingi with alum fixer and in powder condition.Keywords – extraction, spray dryer, fixation, launderometer, and crockmeter